Effect of walking extra distances on the performance of grazing dairy cows in early lactation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science, Massey university, Palmerston North, New Zealand - Pratumsuwan, Sumate (Massey University, 1994)
Two groups, each of 13 Friesian cows in early lactation, were fed and managed identically throughout the experimental period of 4 weeks (13th September-10th October, 1993), except that the control group (CT) walked directly from the paddock to the milking shed and back to the paddock (average 1.5 km per day), whereas the walk group (WK) walked approximately 6 km more per day than the control group (total 7.5 km per day). During walking, all cows were moved at the average walking speed of 55 m/min. The aim of the study was to examine the effects of walking extra distances on the performance of grazing dairy cows in early lactation. A common daily herbage allowance (30-40 kgDM/cow/day) was given to both groups grazed in the same paddock, on equal areas separated by an electric fence. Milk production and composition, somatic cell counts, liveweight and condition score, reproductive performance and grazing behaviour were measured and analysed. Herbage intake was estimated directly using a rising plate pasture meter and indirectly using chromic oxide technique (slow release chromium capsules; CAPTEC NZ., Ltd). The average dry matter intakes, as assessed by the pasture meter, were similar for the CT and the WK group being 16.1 and 16.5 kgDM/cow/day, respectively. Average daily yields of milk and milk solids for both groups were 25 litres/cow and 1.9 kg/cow, respectively. There were no significant differences in milk yields, milk composition, somatic cell counts (SCC), or changes in liveweight and condition score between the two groups. However, the WK group did produce slightly less milk solids (by 2 to 3%), and had slightly higher SCC than the CT group. No adverse effects on reproductive performance of cows in the WK group were observed. Although the WK group spent less time on the pasture by about 1.5 hour per day, there was no significant difference in time spent grazing (GT) between both groups. Nevertheless, the WK group spent significandy less time standing (P<0.001) per day than the CT group, mainly because of less time spent standing/ruminating. The results show that high producing dairy cows in early lactation can walk horizontally (only a small hill was involved), at a comfortable walking speed, up to 7.5 km per day with no significant effects on milk production provided that pasture allowance is not restricted.
Keywords: Milk yield; Dairy cattle; Feeding and feeds; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Animal production::Animal nutrition and management